2023
DOI: 10.3390/genes14061147
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification, Characterization and Expression Analysis of Plant Nuclear Factor (NF-Y) Gene Family Transcription Factors in Saccharum spp.

Abstract: Plant nuclear factor (NF-Y) is a transcriptional activating factor composed of three subfamilies: NF-YA, NF-YB, and NF-YC. These transcriptional factors are reported to function as activators, suppressors, and regulators under different developmental and stress conditions in plants. However, there is a lack of systematic research on the NF-Y gene subfamily in sugarcane. In this study, 51 NF-Y genes (ShNF-Y), composed of 9 NF-YA, 18 NF-YB, and 24 NF-YC genes, were identified in sugarcane (Saccharum spp.). Chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Multiple-sequence alignment analysis showed that the best CsNF-Y proteins contained conserved regions as a result of subunit interactions and DNA binding ( Figure 4 ). These regions are also present in other plants [ 37 ]. Previous studies indicate that the DNA-binding structure of NF-Y can bind to the CCAAT site [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple-sequence alignment analysis showed that the best CsNF-Y proteins contained conserved regions as a result of subunit interactions and DNA binding ( Figure 4 ). These regions are also present in other plants [ 37 ]. Previous studies indicate that the DNA-binding structure of NF-Y can bind to the CCAAT site [ 38 ].…”
Section: Discussionmentioning
confidence: 99%